M-Mode Echocardiographic Studies in Healthy Cats - Brahmwar, Aarush; Hase, Pankaj; Gaikwad, Rajiv; Galdhar, Chandrakant; Pawalkar, Dhananjay; Patil, Manjusha (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
M-mode echocardiography is a non-invasive and indispensible tool for the quantitative evaluation of the heart. Due to domestic cats’ sedentary lifestyles, it has been difficult to diagnose heart disorders in cats since they frequently manifest and exhibit cardiac affections in novel ways. In order to help in the diagnosis of heart disorders in cats, this study was carried out to create baseline reference data in cats (n=12) with mean age of 3.43±1.28 years, weighing 4.43 ±0.45 kg, irrespective of breed and gender, having mean heart rate of 173.67±10.34 beats/min that are bred and fed in India. The M-mode parameters studied with their mean ±SD values were Interventricular septal thickness at diastole (IVSd, 3.50±1.15 mm) and systole (IVSs, 5.65±1.13 mm), Left ventricular internal diameter at diastole (LVIDd, 13.48±2.00 mm) and systole (LVIDs, 7.35±1.15 mm), Left ventricular posterior wall thickness at diastole (LVPWd, 4.53±0.74 mm) and systole (LVPWs, 6.58±0.82 mm), Ejection fraction (EF, 80.55±2.58%), Fractional shortening (FS, 45.50±2.69%), Left atrium (LA, 1.06±0.17 cm), Aorta (AO, 0.86±0.13 cm), LA/Ao ratio 1.25±0.09 and E point to septal separation (EPSS, 1.21±0.51 mm). These baseline values established will facilitate comparison and precise interpretation by the clinician.